IMPROVEMENT OF FERTILITY USING BUSERELIN ACETATE IN REPEAT BREEDING CATTLE - MEHROTRA, S; CHAUDHARl, R K; K, NARAYANAN (The Indian Journal of Animal Reproduction, 2023)
Repeat breeding (RB) syndrome is a frustrating infertility problem in the dairy cow.The present study was planned to observe the efficacy of GnRH analoge on conception rate (CR) in RB cows at the time of insemination.Insemination data were retrieved from breeding records over a period of 44 months. RB cow was selected based on failure to conceive upon 3-5 inseminations and without any palpable abnormality of the reproductive tract and categorized into two groups: Group I cows (n=50) were treated with GnRH analoge (Buserelin acetate, Receptal®, 2.5 mL, i/m) at the time of Al and Group II untreated control (n=50) RB cows. Pregnancy diagnosis was done by rectal palpation at 60 days post breeding. The association between GnRH administration and CR in RB cow was analyzed by using Chi-Square test at 5% level of significance. In treatment group CR was recorded as 32% (16/50) whereas in control group the corresponding figure was 20% (10/50). No significant difference was found between GnRH treated and untreated RB cows with respect to CR (P> 0.05); however, CR was 12% higher in GnRH treated cows.In conclusion, an apparent increase in the CR in GnRH treated RB cows is socially important in India where cow slaughter is banned in many states, besides rescuing the elite high yielding animals from involuntary culling .